Alternative models and numerical simulations of rarefied gas flow in vacuum systems. (October 2018) - Pitakarnnop, Jeerasak; Wongpithayadisai, Rugkanawan; Phanakulwijit, Suwat
Highlights: Rarefied gas flow through leak artefacts is studied basing on the existing approaches. The results are compared with the experimental results from the recognized NMIs. Easy-to-use slip-flow models are valid until the beginning of the transition regime. Beyond the limit of slip-flow models, the kinetic models are recommended. The described approaches are useful for the design of leak artefact and standard. Abstract: An analytical and a numerical studies of rarefied gas effects on the flow through a vacuum pipe and a rectangular microchannel at low operating pressure are performed by the use of both existing continuum and kinetic approaches. The pipe and the channel operates in a high-Knudsen-, low-Reynolds- numbers regime where the viscous effects as well as the rarefied gas effects dominate the flow. Since only the isothermal flow is focused, the slip-flow at the wall is the main anomaly. The paper shows the implementation of both approaches to predict a rarefied gas flow through a leak artefact. The results from various existing models are compared with the experimental results of a flow through leak artefacts, which were performed by recognized national metrology institutes (NMIs). Pros, cons and the limitation of each approach are pointed out.